KARAKTERISTIK PEMASARAN AYAM BROILER PADA BEBERAPA SKALA PEMELIHARAAN DI KOTA KUPANG - Defrys R. Tulle; Johanis A. Jermias; I Ketut Jaya; Tri A. Y. Foenay (Partner, 2009)
A Survey was conducted in  Kupang City.  It was carried on April 2007 to October 2007. Fifty five farmers were  taken as respondents by purposive  random sampling and the market institution respondents were taken by snow ball effect method. The objectives of this study were: (1) to identify broiler marketing distribution at different scale of production, 2) to count the marketing margin and to analyse the factors which affected marketing margin, 3) to know the cost and profit share in each market institution and farmer share, and 4) to assist the broiler marketing efficiency in Kota Kupang. Variables measured consisted of: selling capacity, selling price at farmer level; selling price at consumer or retailer level,  selling price and the cost  at each market institution, sum of trader, and others non technical aspects in marketing activities. Data were analysed  descriptively, and the other by counting of marketing margin, profit share, farmer share and regression analysis. The results of this study indicated that: 1) there were four types of marketing distribution, bigger of production scale, more type of marketing distribution, 2) the higher of production scale, the lower of marketing margin. Based on profit and profit ratio, the marketing efficiency at big scale of production more efficiently than small scale, 3) presentation of farmer share is relatively high and increase following the scale of production, and 4) simultaneously the marketing margin  was affected significantly (p<0.01) by selling capacity, broiler price, sum of trader and marketing cost. Furthermore, partially, marketing margin was affected significantly (p<0.05) by selling capacity and broiler price.Key words: Marketing, Broiler